Development of Drill Shooting Training Aid at Futsal Club in Wonosobo Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The study aimed to make a drill shooting exercise tool. The subjects in this study were two media experts, two futsal experts, and 40 futsal athletes for product testing. The technique of collecting data uses interviews, observation, questionnaires, and documentation. The data analysis technique uses choices with a 1-5 Likert scale, which is very less, less, sufficient, right, and very good. The product effectiveness test gets a 20% increase in shooting practice and a 28% increase in the number of goals, meaning that the product is used. The product trial on stage 1 media experts gave an average score of 3.35 including the